POTENSI DAN PEMANFAATAN PEKARANGAN MENDUKUNG KETAHANAN PANGAN RUMAH TANGGA DI DESA DARU KECAMATAN KAO UTARA - Yeane Kastanja, Ariance; Patty, Zeth; Dadalaka, Iranto (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
The community service activities that have been carried out in Daru Village, North Kao sub-District, aims to provide knowledge for the community about the use of the yard, by farming using a verticultural system that is useful for improving the quality of food and the family's economy. The method used in this service activity is counseling about the management of the yard with a verticultural cultivation system. Participants in this activity were the Daru Village PKK Team, Daru Village Youth and the people who had the desire to cultivate the yard, especially those who can use it for the cultivation of vegetables in the yard. The results of community service activities show that there has been an increase in the knowledge of the PKK Team and Village Youth Groups in utilizing the yard, especially plant cultivation with a verticultural system by utilizing materials that are around the home and village environment.